ROLE OF GLOBALIZED APPROACH FOR SUSTAINABILITY DEVELOPMENT IN HUMAN LIFE - Chaudhary, Srishtee; Mehra, Rajesh (PEOPLE: International Journal of Social Sciences, 2018)
Sustainable development is a complex, interdisciplinary and multidimensional issue dealing with various aspects of environment and social, considering the future of the planet. In this paper sustainability development is presented with its goals to be achieved with respect to planet’s future and limitations encountered for the same. The globally changing scenario leading to over utilization of resources and its effect on environment is discussed with respect to some examples. The limitations regarding current world scenario is discussed and various ideas are proposed for sustainable development. Also latest examples for sustained environment resources are being observed. The concept of organic electronics for sustainable eco-friendly world is conferred.